Assessment of the Performance of Aquaponics and its Uptake for Integrated Fish and Plant Farming in Sub-Saharan Africa - Ani, J. S.; Masese, F. O.; Manyala, J. O.; Fitzsimmons, K. (Africa Environmental Review Journal, 2021)
Aquaponics is an innovative and sustainable fish and vegetable production system that has the potential to contribute to food security and livelihoods of many people in sub-Saharan African (SSA) countries that are experiencing pervasive droughts, declining crop yields, soil pollution, and climate change. Although an emerging innovation in many parts of the world, aquaponics has a huge potential for adoption in SSA countries. Aquaponics, as a technology, is based on the concept of efficient nutrient retention, reduction in water use, and waste discharge to the environment. Aquaponics is also expected to improve profitability by simultaneously producing two cash crops (mainly fish and vegetables). Several freshwaters, marine, and brackish water fishes can be reared in aquaponic systems. A variety of plants can also be grown in combination with fishes, ranging from green leafy vegetables and herbs to fruit plants. Plants utilize nutrients from fish excretion and egestion, and remnants of feeds, and in the process reduce the amount that would otherwise be released in wastewater. To achieve optimum fish and plant growth, maintaining optimal water quality conditions in aquaponic systems is a prerequisite. The amount of nutrients supplied in the system is directly related to the amount of feeds given to fish and the amount of waste produced by fish during excretion and egestion. This review shows that despite the huge potential of aquaponics to improve food security and livelihoods of people in SSA, its adoption is very limited. There is a need for investment in the research and training of farmers and practitioners on the practice and benefits of aquaponics as a sustainable food production system. This review highlights the performance and operation of aquaponics and assesses the constraints to its adoption in SSA countries, including Kenya. The review also identifies knowledge gaps that need to be addressed and gives recommendations on how to make aquaponics more sustainable as a food production system in SSA.